2022
DOI: 10.3389/fpls.2022.1022984
|View full text |Cite
|
Sign up to set email alerts
|

Is allelochemical synthesis in Casuarina equisetifolia plantation related to litter microorganisms?

Abstract: Productivity decline of Casuarina equisetifolia plantation and difficulty in natural regeneration remains a serious problem because of allelopathy. Previous studies have confirmed that 2,4-di-tert-butylphenol (2,4-DTBP) are the major allelochemicals of the C. equisetifolia litter exudates. The production of these allelochemicals may derive from decomposition of litter or from the litter endophyte and microorganisms adhering to litter surfaces. In the present study, we aimed to evaluate the correlation between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…(2001) had concluded that Casuarina equisetifolia , a tree with high resistance against abiotic stress and important in coast line protection, had allelopathic properties in that phenolics, in particular, 2,4-di-tert-butylphenol (2,4-DTBP), released from the photosynthetic branchlets and litter of the tree adversely affected the understorey vegetation. Recently, Xu et al. (2022) suggested that actually, litter fungi with higher abundance in young and mature plantations were involved in the synthesis of 2,4-DTBP.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(2001) had concluded that Casuarina equisetifolia , a tree with high resistance against abiotic stress and important in coast line protection, had allelopathic properties in that phenolics, in particular, 2,4-di-tert-butylphenol (2,4-DTBP), released from the photosynthetic branchlets and litter of the tree adversely affected the understorey vegetation. Recently, Xu et al. (2022) suggested that actually, litter fungi with higher abundance in young and mature plantations were involved in the synthesis of 2,4-DTBP.…”
mentioning
confidence: 99%
“…In 2001, Batish et al (2001 had concluded that Casuarina equisetifolia, a tree with high resistance against abiotic stress and important in coast line protection, had allelopathic properties in that phenolics, in particular, 2,4-di-tert-butylphenol (2,4-DTBP), released from the photosynthetic branchlets and litter of the tree adversely affected the understorey vegetation. Recently, Xu et al (2022) suggested that actually, litter fungi with higher abundance in young and mature plantations were involved in the synthesis of 2,4-DTBP. Based on rhizobiome metagenomics, Wang et al conclude that a decrease of actinobacteria from 10 key genera led to reduced metabolic capacity of the soil microbiome for nutrient cycling together with reduced ion exchange capacity of the rhizosphere soil.…”
mentioning
confidence: 99%